Estrategias lúdicas y su relación en la Discalculia, de los estudiantes de sexto año, de la escuela de Educación Básica “21 de Abril” de la ciudad de Riobamba, período enero - septiembre 2015. - Norma Rocío, Parreño Balarezo (2017)
The present study with the title “Play strategies and their relationship in dyscalculia”, comes from troubles in the learning of mathematics process such as dyscalculia, This research was carried out with the main objective of demonstrating how the guide of play strategies decreases the dyscalculia of sixth year students, at school “21 de Abril” in Riobamba during academic period January - September 2015, From the theoretical point of view “the ludic strategies are instruments that allow to strengthen the activities of learning and resolution of problems”; Methodologically a pre-experimental investigation was developed, besides points to research was: applied, descriptive, field and bibliographic type. This research was carried out with a population of 23 students with dyscalculia problems. General methods were applied such as: the hypothetic-deductive, the inductive and the deductive. These methods were based on observation, a theoretical basis, the establishment and verification of the hypothesis, elaboration of conclusions and recommendations. On the other hand the technique of observation was used and the instrument was the structured observation sheet with ten items related to the research variables. Mention that among the most important achievements is the interest that students show when they manipulate the didactic resources, Deduce, compare and draw their own conclusions, thanks to the application of the Guide to Playful Activities "Playing with Numbers", These achievements facilitated to complement experiences through computer media becoming the teaching of mathematics an highly practical activity.